Role of Multidisciplinary Health Professionals in Infection Control and Prevention: Insights from Nursing, Dental Hygiene, Health Administration, Sociology, and Epidemiology - Abrar Hamad Alnasser; Rusha Abdulrahman Alfriah; Salma Mohammed Alkinani; Reema Khalid Al Dulayqan; Amani Hassan Sharahili; Mariam Habeeb Ali Alhnabi; Nawal Abdullah Aldfire; Saleh Hassan Hadi Al-Wadaei; Fahad Hasan Mohammed Dakam; Yahya Mohammed Hussain Majrashi; Nabil Saud Abdulaziz Aljameel; Tayeb Okais Jubran Qaisi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Infection control and prevention are vital constituents of international healthcare systems, directing to decrease the liability of infectious diseases and increase patient results. This review discovers the role of multidisciplinary health professionals in infection control, concentrating on understandings from nursing, dentistry, dental hygiene, health administration, sociology, and epidemiology. Each discipline adds unique expertise to prevent and achieve infections in clinical and community settings. Nurses act as forefront providers, applying hygiene practices and educating patients to moderate hospital-acquired infections. Dentists and dental hygienists prevent oral infections that can lead to systemic complications, highlighting sterilization and patient education. Health managers confirm effective policy implementation, resource distribution, and submission observing. Sociologists address behavioral and societal factors influencing infection risks, promoting equitable access to healthcare and tailored public health interventions. Epidemiologists analyze infection patterns, assess risks, and provide evidence-based recommendations for preventive measures. By adding efforts from these disciplines, healthcare systems can progress comprehensive strategies to address infection-related challenges. However, challenges such as resource constraints, inconsistent protocols, and communication gaps must be addressed. Future innovations in technology, training, and interdisciplinary collaboration will further enhance infection control efforts.